Rooting of apical, median and basal stem cuttings of Piper aduncum L. on different substrates (Revista de Ciências Agroveterinárias, 2018)
Piper aduncum L. (Piperaceae) is an aromatic species native from Tropical Americas. The elevated dillapiole content in its essential oil attributes great economic potential to the species, due to its proven insecticidal action against important agricultural pests. The domestication and cultivation of this species, seeking the standardization of the essential oil quality, goes through the stage of plant propagation, which presents scarce technical and scientific information. Thus, the objective of this study was to evaluate the rooting of stem cuttings collected from the apical, median and basal positions of P. aduncum plagiotropic branches, in sieved soil, commercial substrate (composed of pine bark, peat, expanded vermiculite and enriched with macro and micronutrients), and vermiculite of medium granulometry. The cuttings were kept under intermittent misting for 45 days until the experimental evaluation. Higher rooting percentages were observed in apical cuttings (17.4%) when compared to basal ones (6.9%). There were also higher number, length and fresh mass of roots in apical cuttings. The substrate did not influence the rooting of P. aduncum stem cuttings.
Keywords: dillapiole; Piperaceae; spiked pepper; vegetative propagation